Implementación de la Mediación Penal en Delitos Menores - Cueva Sánchez, Anahí Elizabeth (2024)
This research paper will analyze the viability, effectiveness, and efficiency of the figure of criminal mediation as an alternative mechanism to the traditional criminal process for cases of minor crimes committed by adults. The aim is to analyze whether mediation is a solution that helps to alleviate the procedural overload, optimize the use of resources, and reduce recidivism. The main objective of this research is to analyze the impact of this modality in the criminal justice system, focusing on the reduction of court overload and the optimization of resources, as well as to analyze the potential benefits offered by criminal mediation in minor offenses for both the victim and the offender and even the benefit for the criminal system, it is intended to demonstrate that this practice not only guarantees a more agile and accessible solution but also contributes to decongest the judicial system, allowing the efficient use of available resources. On the other hand, judicial statistics will also be taken into account, especially the rate of resolution, pendency, and congestion in criminal matters so that accurate data can be obtained to help measure the performance of the courts and prosecutors' offices, to evaluate the effectiveness of the criminal justice system in resolving cases, these rates provide information on the number of cases resolved, the number of pending cases and the number of cases that accumulate in the system, which allows identifying problems and areas for improvement in the criminal justice system. In the section on comparative law, the regulation of the figure of criminal mediation in countries such as Colombia, Spain, the province of Chaco in Argentina, and Mexico was analyzed, the latter country having a specific law focused on the implementation of criminal mediation, as this law was shown to be a very complete regulation that is responsible for regulating different aspects of mediation to make it effective and efficient. 5 In the fieldwork, surveys were made to law professionals in the free exercise of their profession, and interviews with personnel specialized in criminal matters and mediation, it has been determined that there is a procedural overload in the courts and prosecutors' offices, which causes delays in the processes, thus violating constitutional rights and principles. The work ends with propositional guidelines, which suggest the implementation and regulation of criminal mediation through a bill so that criminal mediation is considered a viable alternative to deal with minor offenses to avoid procedural overload, and it should also be taken into account that by making use of this mechanism, the prosecution of minor offenses is avoided, It should also be taken into account that criminal mediation can contribute to the reduction of recidivism by addressing the underlying causes of criminal behavior.